Warthin-Like Papillary Carcinoma of the Thyroid Gland: Case Report and Review of the Literature - Paliogiannis, Panagiotis (Hindawi Publishing Corporation, 2012)
We present a case of Warthin-like papillary thyroid carcinoma in a 22-year-old woman and a review of the literature on the topic. The patient had the occasional discovery of a hypoechoic thyroid nodule of approximately 18 mm, characterized by irregular margins, hyperechoic spots, rich intra- and perilesional vascularization, and a suspicious enlarged right laterocervical lymph node. Fine-needle aspiration was performed for both lesions and the diagnosis of papillary thyroid carcinoma without lymph node involvement was made. The patient underwent thyroidectomy and central neck lymphadenectomy without complications. Histopathological examination suggested a Warthin-like papillary carcinoma of the thyroid gland, with all the removed lymph nodes being free of disease. The patient subsequently underwent iodine ablative therapy and she remains free of disease one year after surgery. Warthin-like papillary thyroid carcinoma is a recently described variant of papillary thyroid cancer that is frequently associated with lymphocytic thyroiditis. Morphologically, it resembles Warthin tumors of the salivary glands, with T and B lymphocytes infiltrating the stalks of papillae lined with oncocytic cells. Surgical and postoperative management is identical to that of classic differentiated thyroid cancer, while prognosis seems to be favourable.